Effects of dietary fiber on the composition, function, and symbiotic interactions of intestinal microbiota in pre-weaned calves - Lu, Wentao; Yi, Xia; Ge, Yuhan; Zhang, Xinyue; Shen, Kaidi; Zhuang, Haohua; Deng, Zhaoju; Liu, Dengke; Cao, Jie; Ma, Chong (Frontiers in Microbiology, 2025)
IntroductionDietary fiber plays a crucial role in maintaining gastrointestinal health. However, its protective effects on the intestinal health of calves remain to be fully elucidated. This study aimed to investigate the impact of dietary fiber supplementation on the intestinal microbiota of pre-weaned calves and its potential role in modulating microbial metabolic pathways.MethodsA randomized controlled trial was conducted, enrolling 135 calves that were randomly assigned into three groups: (1) inulin supplementation, (2) psyllium husk powder (PHP) supplementation, and (3) a control group receiving no dietary fiber. Fecal microbiota samples were collected from calves without diarrhea at five time points (0, 7, 14, 28, and 56 days of age). Metagenomic sequencing was performed to analyze microbial composition and functional pathways. Additionally, a differential analysis of carbohydrate-active enzymes (CAZymes) was performed to evaluate the effect of dietary fiber on carbohydrate metabolism enzyme activity within the intestinal microbiota.ResultsCalves supplemented with dietary fiber exhibited a significant increase in the abundance of Bifidobacterium and Prevotella compared to the control group. These bacterial genera contributed to intestinal protection by modulating secondary bile acid metabolism and flavonoid metabolism pathways. CAZymes differential analysis revealed an increased abundance of carbohydrate metabolism enzymes in response to dietary fiber supplementation, with distinct microbial community compositions observed among different fiber treatments. Notably, at 56 days of age, calves fed PHP harbored intergeneric symbiotic clusters comprising Clostridium, Prevotella, and Bacteroides, suggesting a cooperative microbial network that may contribute to intestinal homeostasis.DiscussionThe findings of this study highlight the beneficial effects of dietary fiber on calf intestinal microbiota, particularly in enhancing microbial diversity and enzymatic activity related to carbohydrate metabolism. The observed microbial symbiosis in PHP-fed calves suggests a potential role in maintaining intestinal homeostasis. These insights provide a theoretical foundation for optimizing dietary interventions to promote gut health in calves during the transition period. Further research is warranted to explore the mechanistic interactions between dietary fiber, gut microbiota, and host health outcomes.